The Practice of Isbat Nikah and Its Implications for Family Status in the Study of Maslahah Mursalah - Alfirdaus, Saifullah; Arsyad, Mufid; Santoso, Haris (al-Rasῑkh: Jurnal Hukum Islam, 2025)
The phenomenon of marriages that are only carried out religiously without state registration still occurs a lot in Way Kenanga District, West Tulang Bawang Regency, causing unclear legal status of families and limited access to civil rights. This study aims to analyze the impact of the practice of marriage confirmation on family status from the perspective of Maslahah mursalah in Islamic law. The study used a qualitative method with case studies, data collection techniques through interviews, observations, and documentation, and was analyzed using a deductive approach using the theory of Maslahah mursalah as the main foundation. The results of the study indicate that marriage confirmation is effective in providing formal legality, strengthening family civil rights, and increasing the social legitimacy of married couples. This practice also fulfills the principles of maqashid al-syari’ah, especially in maintaining offspring and protecting individual rights. The study recommends the need to increase legal socialization programs, simplify marriage confirmation procedures, and provide financial support from the government for low-income communities, in order to expand the benefits of marriage confirmation for the welfare of society in a sustainable manner.